Leaf gas exchanges responses of atemoya scion grafted onto Annona rootstocks - Baron, Daniel; Amaro, Amanda Cristina Esteves [UNESP]; Campos, Felipe Girotto [UNESP]; Ferreira, Gisela [UNESP] (Springer Nature, 2018)
We examined the hypothesis that leaf gas exchange of scion is affected by different rootstocks in wood plants. We investigated daily courses of gas exchange and photosynthetic potential using the CO2 assimilation rates as a function of photosynthetic photon flux density, and then assessed CO2 response curves in atemoya scion (Annona × atemoya Mabb.) grafted onto araticum-de-terra-fria [A. emarginata (Schltdl.) H. Rainer var. terra-fria]: ATF, araticum-mirim [A. emarginata (Schltdl.) H. Rainer var. mirim]: ATM, biribá [A. mucosa (Bail.) H. Rainer]: ATB, atemoya (autograft): ATA, and in ungrafted atemoya plants: CTR. Throughout the entire evaluation period, the net assimilation rate (Anet) and stomatal conductance (gs) of CTR plants remained practically constant, being lower than those of grafted plants between 08:00 a.m. and 12:00 a.m., regardless of the rootstock used. Moreover, ATM plants proved to be more efficient in keeping the stomata open, even during the hottest hours of the day, improving Anet and carboxylation use efficiency. However, this occurred at the lowest maximum carboxylation rate of ribulose-1,5-bisphosphate (Vcmáx). Overall, ATF plants presented a low light saturation point and photosynthetic electron transport rates, though increased maximum quantum yield of photosynthesis was observed. Thus, we accept our hypothesis and conclude that grafting might affect the photosynthetic metabolism of the atemoya hybrid, regardless of the combination used, which promotes enhanced Anet and low Vcmáx and light saturation points.
Keywords: Annonaceae; Gas exchange; Grafted plants; Light curves